PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MEMPERKUAT MUTU KINERJA INSTITUSI PENDIDIKAN ISLAM - Nurlaili; Asbiri; Marlina, Leny; Febrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Human resource development (HRD) is one of the fundamental aspects in improving the performance quality of institutions, especially in the context of Islamic education. This study aims to analyze HRD strategies to strengthen institutional performance based on various previous studies. The method used in this research is descriptive with a qualitative approach. Data were obtained from a literature review, including scientific journals, books, and other documents that support the discussion in this article. The results of this study show that effective human resource development (HRD) in Islamic educational institutions involves several important aspects, such as training, skill development, career management, and performance assessment. With good HR management, Islamic educational institutions can improve the quality of graduates, strengthen the performance of educational staff, and enhance the overall competitiveness of the institution. This emphasizes the importance of comprehensive HR management to achieve better educational goals that are relevant to the needs of the times.